2007
DOI: 10.1128/mcb.00461-06
|View full text |Cite
|
Sign up to set email alerts
|

The Yeast PH Domain Proteins Slm1 and Slm2 Are Targets of Sphingolipid Signaling during the Response to Heat Stress

Abstract: The PH domain-containing proteins Slm1 and Slm2 were previously identified as effectors of the phosphatidylinositol-4,5-bisphosphate (PI4,5P 2 ) and TORC2 signaling pathways. Here, we demonstrate that Slm1 and Slm2 are also targets of sphingolipid signaling during the heat shock response. We show that upon depletion of cellular sphingolipid levels, Slm1 function becomes essential for survival under heat stress. We further demonstrate that Slm proteins are regulated by a phosphorylation/dephosphorylation cycle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(92 citation statements)
references
References 63 publications
(106 reference statements)
4
87
1
Order By: Relevance
“…Both mutants exhibited ,40% increase in PtdIns(4)P levels and a 30-40% decrease in PtdIns(4,5)P 2 levels (Fig. 5A). [ 3 H]inositol labeling was also carried out to determine if complex sphingolipid synthesis was perturbed, as previous studies have suggested that phosphatidylinositol phosphate levels are linked to complex sphingolipid levels (Audhya et al, 2004;Kobayashi et al, 2005;Bultynck et al, 2006;Daquinag et al, 2007;Berchtold et al, 2012). Using inositol labeling, similar results were observed with respect to increased PtdIns(4)P levels and reduced PtdIns(4,5)P 2 levels in the mss4 mutants.…”
Section: Induction Of the Flo11p Cell Adhesion Flocculin Is Reduced Isupporting
confidence: 52%
See 1 more Smart Citation
“…Both mutants exhibited ,40% increase in PtdIns(4)P levels and a 30-40% decrease in PtdIns(4,5)P 2 levels (Fig. 5A). [ 3 H]inositol labeling was also carried out to determine if complex sphingolipid synthesis was perturbed, as previous studies have suggested that phosphatidylinositol phosphate levels are linked to complex sphingolipid levels (Audhya et al, 2004;Kobayashi et al, 2005;Bultynck et al, 2006;Daquinag et al, 2007;Berchtold et al, 2012). Using inositol labeling, similar results were observed with respect to increased PtdIns(4)P levels and reduced PtdIns(4,5)P 2 levels in the mss4 mutants.…”
Section: Induction Of the Flo11p Cell Adhesion Flocculin Is Reduced Isupporting
confidence: 52%
“…For example, Slm1p and Slm2p, both PH domain containing PtdIns(4,5)P 2 -binding proteins, interact with TORCs (Audhya et al, 2004;Fadri et al, 2005;Berchtold et al, 2012). Mss4p mediated PtdIns(4,5)P 2 production, Slm1p/Slm2p and Tor kinases are also important for sphingolipid signaling (Audhya et al, 2004;Kobayashi et al, 2005;Bultynck et al, 2006;Daquinag et al, 2007;Roelants et al, 2011;Berchtold et al, 2012;Liu et al, 2012). Starved yeast cells respond to the addition of glucose or ergosterol, the major sterol of S. cerevisiae, by rapid changes in PIPs (Dahl and Dahl, 1985;Kaibuchi et al, 1986;Frascotti et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Proteins in boldface type were analyzed in this study. Daquinag et al 2007). It was further shown that mutations in cnb1, encoding the regulatory subunit of calcineurin, suppress an avo3 temperature-sensitive mutation (Aronova et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This void in our knowledge is beginning to be filled with the realization that these two pathways, along with the calcineurin signaling pathway, modulate the phosphorylation/dephosphorylation cycle of the Slm1 and Slm2 proteins during heat stress to control actin polarization, endocytosis, and sphingolipid metabolism (82)(83)(84).…”
Section: Cellular Processes Regulated By Lcbsmentioning
confidence: 99%
“…Heat stress was recently shown to initiate the dephosphorylation and rephosphorylation of the Slm proteins (83)(84)(85). Dephosphorylation was shown to be mediated by the protein phosphatase calcineurin, which binds to the Slm proteins (82-84) and plays roles in a variety of stress responses.…”
Section: Cellular Processes Regulated By Lcbsmentioning
confidence: 99%